Tetanus vaccination is associated with differential DNA-methylation: Reduces the risk of asthma in adolescence. Issue 51 (12th December 2016) - Janjanam, Vimala Devi; Mukherjee, Nandini; Lockett, Gabrielle A.; Rezwan, Faisal I.; Kurukulaaratchy, Ramesh; Mitchell, Frances; Zhang, Hongmei; Arshad, Hasan; Holloway, John W.; Karmaus, Wilfried
Abstract: Background: Vaccinations have been suggested to be associated with increased risk of allergic diseases. Tetanus vaccination is one of the most frequently administered vaccines as a part of wound management and was also found to be associated with increased serum IgE levels. We hypothesized that the vaccination modifies the risk of allergic diseases through epigenetic changes such as DNA methylation. Method: Data on tetanus vaccination between 10 and 18 years of age was collected from a birth cohort established on the Isle of Wight UK in 1989. DNA methylation data were collected from individuals at different ages (at birth [n = 30], age 10 [n = 34], age 18 [n = 245] and during pregnancy [n = 121]) using the Illumina Infinium HumanMethylation450 K array. Firstly, we performed an epigenome-wide screening to identify cytosine-phosphate-guanine sites (CpGs) associated with tetanus vaccination in 18-year-olds. Secondly, we tested their association with asthma, allergic sensitization, eczema, serum IgE and pulmonary lung function (FVC, FEV1, FEV1/FVC, and FEF25-75%). We then described changes in the methylation of the selected CpG sites over age, and by vaccination status. Results: Tetanus vaccination was found to be associated with decreased methylation of cg14472551 (p value 0.5 × 10 − 5, FDR-adjusted p value 2.1 × 10 − 4 ) and increased methylation of cg01669161 (p value 0.0007, FDR-adjusted p value 0.014). Both CpGs, in turn, were associated with decreased risk of asthma at 18 years of age. Cg14472551 is located in an intron of KIAA1549L, whose protein binds to a B-cell commitment transcription factor; cg01669161 is located between an antisense regulator of the proteasome assembly chaperone PSMG3, and TFAMP1, a pseudogene. Increased methylation of cg01669161 was also associated with decreased serum IgE levels. Conclusion: DNA methylation changes following tetanus vaccination may offer a novel prospect to explain a differential occurrence of asthma in adolescence.